1997
DOI: 10.1161/01.res.81.6.904
|View full text |Cite
|
Sign up to set email alerts
|

Activation of MAP Kinase In Vivo Follows Balloon Overstretch Injury of Porcine Coronary and Carotid Arteries

Abstract: Vascular restenosis involves contraction, proliferation, and remodeling of the arterial wall in response to overstretch injury. Mitogen-activated protein kinases (MAPKs) are implicated in both contraction and proliferation of vascular smooth muscle (VSM), and studies of porcine carotid arterial muscle strips have shown that mechanical stretch leads to the activation of the extracellular signal-regulated kinase (ERK) family of MAPKs in vivo. We, therefore, analyzed the acute effect of mechanical overstretch inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
63
1
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(70 citation statements)
references
References 32 publications
5
63
1
1
Order By: Relevance
“…All these events may occur in the vessel wall after plaque rupture. Although previous reports have demonstrated the activation of MAP kinases in arteries in animal models of balloon injury and neointimal formation, [25][26][27][28] our study provides evidence that TF can link activation of blood coagulation and SMC proliferation. In this respect, inhibition of these new functions of TF may represent a novel, attractive therapeutic target.…”
Section: Discussioncontrasting
confidence: 65%
“…All these events may occur in the vessel wall after plaque rupture. Although previous reports have demonstrated the activation of MAP kinases in arteries in animal models of balloon injury and neointimal formation, [25][26][27][28] our study provides evidence that TF can link activation of blood coagulation and SMC proliferation. In this respect, inhibition of these new functions of TF may represent a novel, attractive therapeutic target.…”
Section: Discussioncontrasting
confidence: 65%
“…Consistent with our finding, very recent studies showed increased profilin-I expression in hypertrophic thoracic aorta and mesenteric arteries of spontaneously hypertensive rats with subsequent elevation in both P-ERK and P-JNK, suggesting that profilin-I may contribute to the vascular remodeling in these rats (Cheng et al, 2011;Zhong et al, 2011). In this context, previous studies suggested that mechanical stretch is closely related to JNK and ERK1/2 activation (Hu et al, 1997;Pyles et al, 1997). These cascades play an important role in remodeling of blood vessels, as well.…”
Section: Role Of Profilin In Vascular Remodeling and Hypertensionsupporting
confidence: 92%
“…The MAPK signaling pathway is considered to be a critical step in the proliferation of VSMCs 12) and Pyles et al reported that MAPKs were activated in response to balloon overstretch injury in porcine carotid arteries. 7) Using balloon injured carotid artery, it was demonstrated that MAPK signaling, especially ERK1/2, is increased and that medial cell replication following injury is reduced by PD098059. 13) ERK1/2 (a MAPK family member) plays a central role on cell growth regulation, and recently this pathway was found to be involved by triggering Ras-Raf activation, MEK phosphorylation, and ERK1/2 phosphorylations in the proliferative effect of PDGF-BB in VSMCs.…”
Section: Discussionmentioning
confidence: 99%
“…6,7) Therefore, an understanding of its inhibition on PDGF-BBstimulated VSMC proliferation is important in terms of developing methods of treating cardiovascular disease.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation